Comparison of local steroid injection into carpal tunnel via proximal and distal approach in patients with carpal tunnel syndrome - Kamanli, A.; Bezgincan, M.; Kaya, A. (Comenius Univ, 2011)
Objective: Carpal tunnel syndrome (CTS) is the most common peripheral neuropathy presented to physicians. There are several non-surgical treatments methods, such as; splinting of wrist, physical therapy modalities, non-steroidal anti-inflammatory drugs ((NSAIDs), injection of corticosteroids, etc. In this study, we aimed to compare the effects of proximal and distal approach to the carpal tunnel regarding the steroid injection application in patients with idiopathic CTS for confirmed nerve conduction studies (NCS). Material and methods: A total of 19 bilateral CTS patients were enrolled in this study and randomly assigned into 1 of the 2 groups according to the local steroid injection (triamsinolone asetonide 20 mg), either via proximal (10 patients, 20 wrist, 1 M, 9 F)) or distal (palmar) approach (9 patients, 18 wrist, 3M, 6 F) into the carpal tunnel. Clinical and NCS examination were done before and at 3 weeks and 3 months after the injection. Also, severity of night pain, muscle strength, disability by Boston carpal tunnel assessment score (BCTS), HAQ were assessed at baseline and at 3 weeks and 3 months after the injection. All patients were used hand-wrist splint during 3 weeks after injection. Results: There were significant reductions in pain and disability scores between the baseline and follow-up periods. There was not a significant difference between the both groups. There were significant improvement in patients' global assessment in patients from the distal injection group. NCSs showed that electrophysiological improvement was slow. Conclusion: This study showed that steroid injection from distal approach (palmar) into the carpal tunnel on patients with CTS is very comfortable, easy, effective and alternative (Tab. 3, Fig. 5, Ref. 11). Full Text in free PDF www.bmj.sk.
Keywords: carpal tunnel syndrome; CTS; electrodiagnosis; steroid; local injection